2007
DOI: 10.1016/j.ijrobp.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

5-Iodo-2-Pyrimidinone-2′-Deoxyribose–Mediated Cytotoxicity and Radiosensitization in U87 Human Glioblastoma Xenografts

Abstract: Purpose-5-iodo-2-pyrimidinone-2′-deoxyribose (IPdR) is a novel orally administered (po) prodrug of 5-iododeoxyuridine (IUdR). As po IPdR is being considered for clinical testing as a radiosensitizer in patients with high grade gliomas, we performed this in vivo study of IPdR-mediated cytotoxicity and radiosensitization in a human glioblastoma xenograft model, U87.Methods and Materials-Groups of 8-9 athymic male nude mice (6-8 weeks old) were implanted with sc U87 xenograft tumors (4 × 10 6 cells) and then rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The IUdR incorporations in our CHO cell experiments had a maximum thymidine replacement of 16 replacements are obtainable-e.g., Lawrence et al (24) reported a maximum of 30% thymidine replacement-such incorporations are probably therapeutically unrealistic. In our experiments, longer incubation times (36 hours) resulted in higher IUdR toxicity but insignificantly greater incorporation because IUdR began to inhibit cell growth.…”
Section: Iudr Uptakementioning
confidence: 96%
See 2 more Smart Citations
“…The IUdR incorporations in our CHO cell experiments had a maximum thymidine replacement of 16 replacements are obtainable-e.g., Lawrence et al (24) reported a maximum of 30% thymidine replacement-such incorporations are probably therapeutically unrealistic. In our experiments, longer incubation times (36 hours) resulted in higher IUdR toxicity but insignificantly greater incorporation because IUdR began to inhibit cell growth.…”
Section: Iudr Uptakementioning
confidence: 96%
“…Whereas rapid division of cancer cells in comparison to their healthy counterparts should result in preferential DNA incorporation in cancer, previous studies have reported in vivo IUdR incorporation levels less than our lowest value of 9.2% thymidine replacement (7,25). However, more recent studies of Kinsella et al (11,16) showed considerable improvement in IUdR uptake when an IUdR derivative with more favorable kinetics was used.…”
Section: Iudr Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…The increased effectiveness of external radiation therapy induced by IUdR incorporation partially occurs via mechanisms related to the biochemistry of DNA damage and repair [1416], corresponding to radiosensitization, and partially through enhancement of the dose directed at DNA from the localized dose created by Auger electrons which corresponds to the photoactivation contribution. This increase depends on the percentage of base replacement and on the initial photon spectrum [4, 6, 1725].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Currently, an oral (po) prodrug of IUdR (5-iodo-2-pyrimidinone-2-deoxyribose, IPdR) is being tested in phase 0/I clinical trials at the National Cancer Institute, based on an improved pre-clinical therapeutic index for po IPdR compared to continuous infusions of IUdR using human glioblastoma xenograft models. 20,21 Over the last decade, our laboratory has found that two different DNA repair pathways, A naturally occurring frameshift mutation resulting in the formation of truncated MED1 having only the MBD has been reported in human gastrointestinal cancers. 31 These truncated proteins, if expressed, would lack the GD but retain the N-terminal half of the protein including the MBD.…”
Section: Discussionmentioning
confidence: 99%